Mental Health Training Module: Education Strategy for Health Cadres in the Community - Warih Andan Puspitosari; Mutia Rofida; Shobiqo Ramdani Putri (Universitas Malahayati Lampung, 2025)
ABSTRACT Mental health problems in Indonesia continue to increase, but many people still do not understand the symptoms and treatment pathways. Health cadres as an extension of health services in the community have an important role in education, early detection, and referral of mental illness cases. Cadres need a mental health module to support their tasks in the community.. This study aims to evaluate the effect of mental health training modules on improving the knowledge of health cadres in the community. This study used a quasi-experimental design with a pretest-posttest approach without a control group. The subjects were 37 health cadres in the working areas of Sewon 2 and Sedayu 1 Health Center, Bantul Regency, Yogyakarta Special Region. Inclusion criteria included active cadres and willing to participate in the training. Exclusion criteria were not attending the full training and incomplete questionnaire filling. The intervention was a one-day training consisting of 3 sessions using a mental health module for cadres developed by the researcher. Data were analyzed using Wilcoxon Signed Rank Test. Most of the subjects were over 40 years old and all were female. The results of the analysis showed a significant increase in the subject's knowledge score after the intervention with a p value (p=0.000), with an effect size value of 0.613. Further analysis showed that the age factor and the length of time as a cadre had a pgt;0.05 value. Training using the Mental Health Module for Cadres is an effective strategy to increase the capacity of health cadres in the community. Contextualized materials and interactive training approaches are key factors in the success of the intervention. Replication and development of the module is needed for a wider and more diverse area. Keywords: Health Cadres, Mental Health, Mental Health Module, Community.